Dual-functional carboxymethyl levan-based protein carrier for cosmeceutical application of human epidermal growth factor - Ko, Hyunjun; Sung, Bong Hyun; Kim, Mi-Jin; Park, Hyun Joo; Sohn, Jung-Hoon; Bae, Jung-Hoon (International journal of biological macromolecules, 2023)
Human epidermal growth factor (hEGF) has been a subject of extensive research as its wide range of physiological functions has many potential applications. However, due to the low stability of hEGF, its physiological effect is easily lost under conditions of use. To compensate for this, we developed a stable delivery system using levan-based nanoparticles. The entrapment yield of various tested proteins was significantly improved by employing carboxymethyl levan (CML) instead of levan; the entrapment yield of the CML-hEGF nanoparticles was 84.1 %. The size and zeta potential of the nanoparticles were identified as 199.9 ± 3.87 nm and −19.1 mV, respectively, using scanning electron microscopy (SEM) and particle size analysis. Dual biological functions of the nanoparticles (skin regeneration and moisturizing) were identified through collagen synthesis activity and aquaporin 3 expression level analysis. Stability of the prepared nanoparticles was also investigated via cell proliferation activity comparison under mimicked physiological conditions. The CML-hEGF nanoparticles maintained cell proliferation activity over 100 % for 6 weeks, while free hEGF was almost inactivated within 2 weeks. Taken together, our results indicate that the CML-based hEGF nanoparticles can be used in pharma- and cosmeceutical applications, guaranteeing a high entrapment capability, functionality, and stability.